Respon Pertumbuhan Protocorm Anggrek Dendrobium nindii X Dendrobium Jaya Srani Dengan Penambahan Berbagai Konsentrasi Benzyl Amino Purin (BAP) Dan Ekstrak Pisang Ambon Secara In Vitro - Unay Nursolihah; Rommy Andhika Laksono; Nurcahyo Widyo Daru Saputro (Peneliti.net, 2022)
This research was conducted at the Laboratory of Tissue Culture, Faculty of Agriculture, University of Winaya Mukti Jln Raya Bandung – Sumedang No. 29, Gunungmanik Tanjungsari District, Sumedang Regency, West Java Province. The time of this research was started from September 2020 to November 2020. The purpose of this study was to obtain the best response to the administration of various concentrations of BAP + Ambon banana extract on the orchid plant Dendrobium nindii X Dendrobium Jaya Srani. The method used is an experimental method with an environmental design, namely a 2 factor factorial completely randomized design (CRD) with 5 replications. The first factor is BAP with 4 levels (0 ppm; 1 ppm; 2 ppm; 3 ppm). The second factor is the Ambon banana extract with 4 levels (0% ; 5% ; 10% ; 15%). Data were analyzed using the F test at 5% level on all observed variables, if the data produced between treatments were significantly different, to find out the highest growth and yield, further tests were carried out with Duncan Multiple Range Test (DMRT) further test data analysis at 5% level. . The results obtained in this study indicate that there is a growth response on the parameters of the number of shoots, number of leaves and number of roots on the protocorm of Dendrobium nindii X Dendrobium Jaya Srani orchids with various concentrations of BAP and Ambon banana extract. The best treatment was found at a concentration of 1 ppm BAP and 5% Ambon banana extract which gave optimal results on the number of leaves with an average of 6.25 leaves, the number of shoots with an average of 5.37 shoo